Strategi China di Kawasan Asia Timur - Purnama, Rafiq (Jurnal Diplomasi Pertahanan, 2020)
The East Asian region has always been warm because of China's dominance in influencingcountries. Some of China's strategies, on the one hand, make regional stability more conducive;on the other hand, its neighbors feel threatened. Therefore, this study aims to look at China'sstrategy in the economic and defense fields and how the neighboring countries react to China'smaneuvers. The method used is content analysis with strong realism views. Seen from the pointof view of realism, China and its surrounding countries' behavior is very relevant, namely thenature of human egoism and greed in various things, especially political realism, which alwaysemphasizes countries to pursue power and fulfill the "national interest" of each country. Chinawill continue to strengthen its influence in the region. This has sometimes made regionalinstability and stability the key to increasing countries' economic growth in the region.Keywords: East Asia, economic and defense strategy, regional stability, realism, nationalinterest